Six generations of CHMP2B‐mediated Frontotemporal Dementia: Clinical features, predictive testing, progression, and survival. (8th January 2022) - Roos, Peter; Johannsen, Peter; Lindquist, Suzanne G.; Brown, Jeremy M.; Waldemar, Gunhild; Duno, Morten; Nielsen, Troels T.; Budtz‐Jørgensen, Esben; Gydesen, Susanne; Holm, Ida E.; Collinge, John; Isaacs, Adrian M.; et al.
Abstract: Objectives: Chromosome 3‐linked frontotemporal dementia (FTD‐3) is caused by a c.532‐1G > C mutation in the CHMP2B gene. It is extensively studied in a Danish family comprising one of the largest families with an autosomal dominantly inherited frontotemporal dementia (FTD). This retrospective cohort study utilizes demographics to identify risk factors for onset, progression, life expectancy, and death in CHMP2B ‐mediated FTD. The pedigree of 528 individuals in six generations is provided, and clinical descriptions are presented. Choices of genetic testing are evaluated. Materials and Methods: Demographic and lifestyle factors were assessed in survival analysis in all identified CHMP2B mutation carriers (44 clinically affected FTD‐3 patients and 16 presymptomatic CHMP2B mutation carriers). Predictors of onset and progression included sex, parental disease course, education, and vascular risk factors. Life expectancy was established by matching CHMP2B mutation carriers with average life expectancies in Denmark. Results: Disease course was not correlated to parental disease course and seemed unmodified by lifestyle factors. Diagnosis was recognized at an earlier age in members with higher levels of education, probably reflecting an early dysexecutive syndrome, unmasked earlier in people with higher work‐related requirements. Carriers of the CHMP2B mutation had a significant reduction in life expectancy of 13 years. Predictive genetic testing was chosen by 20% of at‐risk family members. Conclusions: CHMP2B ‐mediated FTD is substantiated as an autosomal dominantly inherited disease of complete penetrance. The clinical phenotype is a behavioral variant FTD. The disease course is unpredictable, and life expectancy is reduced. The findings may be applicable to other genetic FTD subtypes.